2014
DOI: 10.1017/s0954422414000110
|View full text |Cite
|
Sign up to set email alerts
|

Autism and nutrition: the role of the gut–brain axis

Abstract: Autism spectrum disorder (ASD) is characterised by deficits in the ability to socialise, communicate and use imagination, and displays of stereotypical behaviour. It is widely accepted that ASD involves a disorder in brain development. However, the real causes of the neurodevelopmental disorders associated with ASD are not clear. In this respect, it has been found that a majority of children with ASD display gastrointestinal symptoms, and an increased intestinal permeability. Moreover, large differences in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
16

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 152 publications
2
87
0
16
Order By: Relevance
“…Recently, accumulating evidence suggests that gut microbiota can influence behavior by regulating brain chemistry [22][23][24][25] and the microbiota-gut-brain axis'' became one of the major topics of research interest [6,8]. Although recent few studies revealed that human gut microbiome differs among individuals in correlation with diet, age, antibiotic usage, and underlying conditions [26][27][28][29], up to 60 % of healthy people are thought as asymptomatic carriers of Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, accumulating evidence suggests that gut microbiota can influence behavior by regulating brain chemistry [22][23][24][25] and the microbiota-gut-brain axis'' became one of the major topics of research interest [6,8]. Although recent few studies revealed that human gut microbiome differs among individuals in correlation with diet, age, antibiotic usage, and underlying conditions [26][27][28][29], up to 60 % of healthy people are thought as asymptomatic carriers of Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…Research investigating both brain and gut function has demonstrated that both tissues have various degrees of involvement in ASD progression [5, 9]. A recent unifying theory termed the “gut-brain axis” outlines the interactions between the brain and microbiome, suggesting a possible connection in ASD [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…A recent unifying theory termed the “gut-brain axis” outlines the interactions between the brain and microbiome, suggesting a possible connection in ASD [9, 10]. This research proposes that disruption to gut microbiota composition or diversity can modulate behavior and neural biochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Many processes in the gut and nervous systems may be interconnected. Previous research has suggested that some, perhaps many, children with autism have abnormal communities of digestive bacteria in their intestines 10 .…”
Section: Microbiomementioning
confidence: 99%